FACTORS OF GROWTH OF THE EFFICIENCY OF PUBLIC DEBT MANAGEMENT - M. E. Kosov (Publishing House of the State University of Management, 2021)
Public debt is an integral part of public finances of various countries, the process of its management, including formation, maintenance and repayment has a powerful impact on the macroeconomic system of the state. The subject of the study is the public debt of the Russian Federation. The article performs a correlation and regression analysis of factors that have a direct impact on the state of the Russia’s public debt under the conditions of the restrictions caused by the Covid-19 coronavirus infection, as well as the consequences of these restrictions. The paper proposes an econometric model that describes a system of indirect macroeconomic factors that are not directly related to the state’s debt policy, but show the strongest influence on the formation of public debt in modern realities and increase the efficiency of its management, as well as reflect the quality of public financial management in general. The author concludes that the demographic burden and the indicator reflecting the ratio of the budget deficit to the total budget revenue have the greatest impact on the effectiveness of public debt management.